Influência de procedimentos restauradores e endodônticos nadistribuição de tensões analisada pelo método dos elementosfinitos tridimensional - Floriano Jorge Cardoso Bello (2004)
The preservation of a healthy dental structure is important for the maintenance of the integrity and balance of the mastigatory system. The purpose of this study was to evaluate the stress distribution in a maxillary central incisor induced by the preparation cavity, and endodontic and restorative procedures when submitted load through element finite threedimensional models. Model 1 constituted of enamel, coronary and radicular dentine, pulp, and cortical and spongy bones. In models 2 to 5 dentine and enamel were removed to simulate preparation cavities. In models 6 to 9 the teeth from models 2 to 5 were restored with composite resin. In model 10 a pin was placed intra-canal, while the 4 mm remaining to the root apex was filled with gutta-percha. Stress analysis in all models was conducted via the finite element method. A static load of 100N was applied at a 45 degree inclination to the incisors edge. The results showed an increase in the stress concentration in all of thepreparations cavities as well as in the endodontic access. Applying conservative interproximal preparations lead to an increment of more than 79% in the stress concentration as compared to the intact tooth. Moreover, preparation of the endodontic access on the same tooth resulted in an increment of more than 98% in the stressconcentration, indicating that the endodontic access exacerbates the stress concentration in interproximal preparations. On the other, the use of extensive interproximal preparations resulted in an increase in stress concentration of 134% in relation to the intact tooth, this reaching 173% increase when associated with the endodontic access. When applied on its own, the endodontic access leads to an increase of 116% on the stress concentration as compared to the intact tooth. Associated with a extensive interproximal preparation this value increase for 118%. An increase of 127% happened when the access endodontic was 110 applied with both extensive and conservative interproximal preparations being present at the same time. Placing a stainless steel pin increased the stress concentration in 16 times as compared to the intact tooth. The models indicated that subsequent reduction of the dentalstructure always resulted in an increase stress concentration in the cavity areas. Restoring the interproximal preparations and the access endodontic with composite resin resulted in biomechanics conditions similar to the pattern of the intact tooth